'Waging War on the Streets': the Irish Women Patrol, 1914–22.1. Issue 154 (November 2014) - Pašeta, Senia
Abstract : Female activists across the United Kingdom had insisted from the late nineteenth century that the employment of women police who would deal with problems specific to women and children could help to address pressing social questions, or at least to offer women some protection within the entirely male criminal justice system. Their campaign for women police was connected to similar demands for the employment of female prison visitors and inspectors and, later, jurors and lawyers, and it was predicated on the idea that neither prisons nor courts afforded women fair and equal treatment under the law. Early victories included the appointment of police matrons and searchers, but the resistance of police authorities and most other civil servants to female officers remained solid into the early twentieth century, feminist campaigning notwithstanding. The outbreak of the First World War, however, provided an ideal context for renewed activism on the issue, not least because commentators across the British Isles predicted that the apparent inability of girls and young women to resist the lure of uniformed men would lead to outbreaks of war-induced sexual promiscuity and a decline in standards of public behaviour.